Global kidney disease - Herrera Añazco, Percy (2014)
We read with interest the Lancet Series on Global Kidney Disease. Valerie Luyckx and colleagues describe the economics and medical management of chronic kidney disease in sub-Saharan Africa.1 We note clear similarities with patients in Peru. Indeed, in Peru, the Ministry of Health (MINSA)—which covers 70% of the population—does not have a comprehensive programme for the management of patients with chronic kidney disease, including renal replacement therapies. However, the Social Security System (Essalud)—which covers 20% of the population—has a chronic kidney disease programme.